Transcervical resection of endometrium as a conservative management of dysfunctional uterine bleeding in premenopausal patients - Pote, Girish A.; Raut, Namita Nandkumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Dysfunctional uterine bleeding (DUB) affects 10% to 15% women of reproductive age group. A prospective observational study was performed to study the efficacy, rate of satisfaction and adverse effects of Transcervical resection of endometrium (TCRE) in the treatment of DUB in premenopausal women. Methods: 30 patients with DUB attending the hospital underwent TCRE and patients were followed up after 6 week, 3 months, 6 months up to 1 year and there bleeding score was calculated. Their response to treatment, complications and satisfaction rate were studied. Results: 43.3% of the women in this study were in the age group of 40-44 years. Post TCRE, 43.33% (n=13) had hypomenorrhea. 33.33% (n=10) had regular cycle, 13.33% (n=4) women had amenorrhea and 10% (n=3) had no response and underwent hysterectomy. 86.66% (n=26) women were satisfied with the treatment whereas 13.33% (n=4) were not satisfied. One patient had uterine perforation and serosal bowel injury due to extended cautery injury. Bleeding reduced considerably and a statistically significant (paired t-test, p-value <0.05) difference was observed in pre and post procedure (6 weeks, 3 months, 6 months and 1 year) bleeding scores. Conclusions: Considering advantages like shorter operative time, uterine conservation and early mobility TCRE is a procedure of choice in patients in whom hysterectomy is either technically difficult or medically contraindicated or in those who are not suitable for long term medical management.